Right place, right time, and only once: replication initiation in metazoans. - Machida, Y.J.; Hamlin, J.L.; Dutta, A. (Cell, 2005)
DNA replication is tightly regulated at the initiation step by both the cell cycle machinery and checkpoint pathways. Here, we discuss recent advances in understanding how replication is initiated in metazoans at the correct chromosome positions, at the appropriate time, and only once per cell cycle.